Metabolic engineering and potential functions of proanthocyanidins in poplar - Mellway, Robin D (Landes Bioscience, 2009)
Poplar (Populus spp.) is a widely distributed tree genus of significant economic and ecological importance. Poplar trees accumulate proanthocyanidins (PAs) in leaves, roots, and a variety of other tissues. Damage to leaves by insects causes a rapid accumulation of PAs, both at the site of damage and distally in undamaged leaves. This rapid PA accumulation is mediated by the activation of genes encoding enzymes involved in PA synthesis. PAs have been hypothesized to deter insect feeding and reduce the nutritive value of poplar leaf tissue, but experimental evidence supporting a role for PAs as an effective inducible defense against herbivores is lacking. Our recent paper described the identification of a MYB gene that regulates the PA pathway under multiple stress conditions, and we used this gene to constitutively activate the PA pathway in poplar. Here we describe observations that suggest that poplar PAs may have roles besides insect defense, for example, responses to UV light. The PA-modified trees will be a useful tool for analyzing the biological roles of PAs in this important model tree.